Primary Segmental Volvulus of Small Intestine: Surgical Perspectives According to Age at Diagnosis - Soo-Hong Kim; Yong-Hoon Cho; Yong-Hoon Cho; Hae-Young Kim (Frontiers Media S.A., 2019)
Background: Small intestinal volvulus often occurs with malrotation. However, in some cases, it could develop without any other clinical conditions, and this is called primary segmental volvulus (PSV) of the small intestine. Two types of PSV (early and late neonatal) have been described previously, especially in preterms. Moreover, there were other cases occurring beyond the neonatal period.Methods: The medical records of 14 cases definitively identified as PSV were retrospectively reviewed. The patients were divided into 2 groups according to postnatal age at diagnosis: neonatal group and beyond neonatal group. Then, the 2 groups were compared in terms of clinical features.Results: There were 11 patients in the neonatal group (78.6%) and 3 patients in the beyond neonatal group (21.4%). There were no differences in gestational age, birth weight, and ratio of prematurity. In the neonatal group, the antenatal abnormal sonographic findings were found more frequently and the perforation of the involved segment were relatively common. Meanwhile, the involved segment was confined to the ileum and more commonly associated with mesentery change in the beyond neonatal group. There was no mortality.Conclusion: The 2 clinical types of PSV according to postnatal age at diagnosis show some differences in clinical features. Moreover, PSV should be considered a possible cause of surgical problems beyond the neonatal period.